Thermal Regulation of the Brain—An Anatomical and Physiological Review for Clinical Neuroscientists - Wang, Huan; Kim, Miri; Normoyle, Kieran P.; Llano, Daniel (Frontiers in Neuroscience, 2016)
Humans, like all mammals and birds, maintain a near constant core body temperature of 36–37.5°C over a broad range of environmental conditions and are thus referred to as endotherms. The evolution of the brain and its supporting structures in mammals and birds coincided with this development of endothermy. Despite the recognition that a more evolved and complicated brain with all of its temperature-dependent cerebral circuitry and neuronal processes would require more sophisticated thermal control mechanisms, the current understanding of brain temperature regulation remains limited. To optimize the development and maintenance of the brain in health and to accelerate its healing and restoration in illness, focused, and committed efforts are much needed to advance the fundamental understanding of brain temperature. To effectively study and examine brain temperature and its regulation, we must first understand relevant anatomical and physiological properties of thermoregulation in the head-neck regions.